Yarrowia lipolytica chassis strains engineered to produce aromatic amino acids via the shikimate pathway - Macarena Larroude; Jean‐Marc Nicaud; Tristan Rossignol (Microbial Biotechnology, 2021)
Summary Yarrowia lipolytica is widely used as a microbial producer of lipids and lipid derivatives. Here, we exploited this yeast’s potential to generate aromatic amino acids by developing chassis strains optimized for the production of phenylalanine, tyrosine and tryptophan. We engineered the shikimate pathway to overexpress a combination of Y. lipolytica and heterologous feedback‐insensitive enzyme variants. Our best chassis strain displayed high levels of de novo Ehrlich metabolite production (up to 0.14 g l−1 in minimal growth medium), which represented a 93‐fold increase compared to the wild‐type strain (0.0015 g l−1). Production was further boosted to 0.48 g l−1 when glycerol, a low‐cost carbon source, was used, concomitantly to high secretion of phenylalanine precursor (1 g l−1). Among these metabolites, 2‐phenylethanol is of particular interest due to its rose‐like flavour. We also established a production pathway for generating protodeoxyviolaceinic acid, a dye derived from tryptophan, in a chassis strain optimized for chorismate, the precursor of tryptophan. We have thus demonstrated that Y. lipolytica can serve as a platform for the sustainable de novo bio‐production of high‐value aromatic compounds, and we have greatly improved our understanding of the potential feedback‐based regulation of the shikimate pathway in this yeast.